Comparison of SpO2/FiO2 and PaO2/FiO2 ratios as markers of acute lung injury - Dewi Shandi Laila; Chairul Yoel; Hakimi Hakimi; Munar Lubis (Paediatrica Indonesiana, 2017)
Background One of the diagnostic criteria for acute lung injury (ALI) is the PaO2/FiO2 (P/F) ratio. This measurement is obtained by blood gas analysis, which involves an invasive procedure (arterial blood draw). In order to reduce invasive procedures on critically ill patients, an alternative non-invasive marker for ALI is needed. The SpO2/FiO2 (S/F) ratio attained by pulse oximetry may be a suitable alternative.Objective To investigate for a correlation between S/F ratio and P/F ratio, in order to find an alternative non-invasive marker of ALI.Methods A cross-sectional study was conducted in the pediatric intensive care unit (PICU) at Haji Adam Malik Hospital, Medan from August 2012 to June 2013. Subjects (children aged 1 month – 18 years) underwent blood gas analysis when their pulse oximetry showed saturation of 80-97% within 24 hours of ventilator use. We measured PaO2, SpO2, and FiO2 and calculated S/F and P/F ratios. Data were analyzed by Spearman’s correlation and linear regression tests.Results Of 69 PICU patients, 39 children fulfilled the criteria for ALI. The S/F ratio and P/F ratio had a weak correlation (r=0.2; P=0.18). The linear regression equation was S/F ratio = 129.67 + 0.11 (P/F), with S/F ratio values of 162.67 and 151.67 correlating to P/F ratio values of 300 and 200, respectively.Conclusion  The S/F ratio has a weak correlation with P/F ratio for ALI in children.